Independensi Penentuan Jumlah Nilai Agunan dalam Perjanjian Kredit yang Dilakukan oleh Appraisal Bank - Elysabet Sry Devi Bruni Simatupang; Sunarmi S; Mahmul Siregar; Utary Maharany Barus (LPPM Universitas Malikussaleh, 2021)
A bank always requires collateral to its customers in providing credit facility as a form of a guarantee or responsibility for their contract with the bank. A bank also employs an Appraisal Bank or Public Appraisal Service Office (KJPP). KJPP is expected to prevent wrong collateral valuation and value engineering. Therefore, the research problems are how the independence of an Appraisal Bank is, in performing collateral valuation in a credit contract, how the binding force of the valuation results gained by an Appraisal Bank to the collateral in a credit contract, and how the liability of the Appraisal Bank for the valuation performed by an Appraisal Bank to the collateral in a credit contract. This is a normative juridical and descriptive research. This research employs statutory method using primary, secondary, and tertiary legal materials. The data are collected from library study and field observation. They are analyzed by reducing data, presenting data, and drawing conclusions/making verification to obtain descriptive data. The results of the research conclude that the independence an. appraisal is assessed when he performs valuation without intervention from anyone. In legal view, an appraisal is considered valid and affecting the collateral object; the results of his valuation becomes his responsibility. The responsibility of an appraisal for his valuation results can be seen from the conformity of his report and the prevailing regulations. It is suggested that one be required and obliged to have specific skills, integrity, honesty and objectivity to become an appraisal. An appraisal also has to be guided by ethical codes and prevailing laws and regulations.